Bootstrapping reliable noise measure in time-gated nuclear magnetic resonance data. Issue 1 (1st December 2018) - Irons, Trevor P.; McPherson, Brian J.O.L.; Kass, M. Andy
Abstract : Time gating is a commonly used approach in the pre-processing of nuclear magnetic resonance (NMR) data before Laplace inversion. Gating suppresses spurious signals that can degrade recovered decay time distributions and therefore often stabilizes inversion. However, care must be taken in applying this technique to real world data where both non-Gaussian and correlated noise decrease the efficacy of noise reduction through stacking. If not properly accounted for, unreliable noise estimates introduce inversion artefacts. Fortunately, noise realization proxies obtained through data phasing can be used to bootstrap reliable confidence intervals for the windowed data. Benefits of the approach are demonstrated through inversion of synthetics as well as borehole data from a deep carbon capture and sequestration application. We also introduce an open source cross platform data processing utility with these capabilities which interested persons can use to explore the impacts of various processing workflows.